ANALISIS STRATEGI DINAS KOPERASI UKM DAN TENAGA KERJA DALAM MENANGGULANGI PENGANGGURAN DI KABUPATEN KEPUALAUAN TALAUD - ANASTASYA BUNGKURAN; GUSTAAF BUDI TAMPI; RULLY MAMBO (Sam Ratulangi University, 2022)
This study aims to see the extent of the local government's strategy in dealing with unemployment in the Talaud Islands Regency and see what are the obstacles to the local government in overcoming unemployment in the Talaud Islands Regency. The type of research used is descriptive qualitative research. Based on the results of the study, it shows that, for the objectives or targets that have been implemented properly by prioritizing the unemployed community in every existing policy strategy, the policy strategies that have been made and are being implemented in tackling unemployment in the Talaud Islands Regency have not been able to overcome unemployment because not all the unemployed community that can be reached with the policy strategy that is being implemented, and for the activity stages of the policy strategy being implemented, it can be seen from the activities that have been carried out in order to support the policy strategy that is being carried out by the Regional Government.Â Keywords: Unemployment, strategy, SME Cooperative Service and Manpower